2006
DOI: 10.1007/s10552-005-0500-6
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific Fluoride Exposure in Drinking Water and Osteosarcoma (United States)

Abstract: Our exploratory analysis found an association between fluoride exposure in drinking water during childhood and the incidence of osteosarcoma among males but not consistently among females. Further research is required to confirm or refute this observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(113 citation statements)
references
References 24 publications
3
104
1
5
Order By: Relevance
“…Similarly, case-control studies have not found any significant association between osteosarcoma risk and fluoridated drinking water (McGuire et al, 1991;Moss et al, 1995) or total lifetime fluoride (Gelberg et al, 1995). One exploratory analysis reported an increased risk among a subset of males exposed to fluoride in drinking water during childhood (Bassin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, case-control studies have not found any significant association between osteosarcoma risk and fluoridated drinking water (McGuire et al, 1991;Moss et al, 1995) or total lifetime fluoride (Gelberg et al, 1995). One exploratory analysis reported an increased risk among a subset of males exposed to fluoride in drinking water during childhood (Bassin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of epidemiologic studies speculated the unintentionally http://dx.doi.org/10.1016/j.aca.2014.02.026 0003-2670/© 2014 Elsevier B.V. All rights reserved. chronic overexposure to F − account for many medical issues including fluorosis and osteosarcoma [2][3][4]. To avoid the adverse health problems caused by the uptake of F − from water, government authority, for example, the United States Environmental Protection Agency (USEPA) set a standard of 1 g mL −1 to protect against osteofluorosis and dental fluorosis, whereas 2 g mL −1 is considered as health-risk and 4 g mL −1 as the maximum contaminant level (MCL) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Gelsolin is involved in various biological functions such as apoptosis stimulator, cell motility, inflammation and wound healing (68). the incidence of osteosarcoma and fluo ride exposure in drinking water during childhood (57). However, their finding is only consistent among male subjects.…”
Section: Biomarker For Bone Tumors From Genomics and Proteomics Studiesmentioning
confidence: 96%